Przemiany seksualnościw społeczeństwie współczesnym. Teoria i rzeczywistość - Redakcja (Wydawnictwo Naukowe UAM, 2014)
Publication Transformation of Sexuality in Contemporary Society. Theory and Reality has an interdisciplinary character. Human sexuality is presented in the perspective of the educational, social, psychological and medical assistance. The authors of the articles are specialists in various fields of science, many of them are known in Polish and foreign sexological literature. The book consists of four parts, dealing successively with important issues from a wide area of sexology. The main objective of this division was the reader’s interest in a specific context of sexual functioning including interdisciplinary perspectives, both theoretical and empirical. In the first part, entitled “Reconstructions of Sexuality. Contexts and Discourses” the authors attempt to reconstruct the events that relate to the foundations – essentials (health, therapy, body, identity, history) related to the discussed issues. The second part is devoted to the subject of sex education. The next part deals with issues related to sexual life from the perspective of developmental lines. The final section discusses the issues related to human sexuality from the socio-cultural perspective. The authors of texts contained in this book are representatives of different disciplines: medicine, education, psychology, sociology and law. However, despite the differences in terms of education, what they share is a scientific and clinical interest in the man and one’s functioning in the sphere of sexual life.

Publikacja o charakterze interdyscyplinarnym. Seksualność człowieka jest w niej przedstawiona w perspektywie edukacyjnej, społecznej, psychologicznej i medycznej. Autorami artykułów są specjaliści z różnych dziedzin nauki, wielu z nich jest znanych w polskim i zagranicznym piśmiennictwie seksuologicznym. Praca wpisuje się w nurt naukowych dyskursów nad kształtem i formą seksualności człowieka na różnych etapach życia. Jednocześnie pozycja ta zawiera wiele cennych klinicznie informacji, które mogą być przydatne dla pedagogów, psychologów, lekarzy w ich praktyce edukacyjnej i terapeutycznej.
Transformation of Sexuality in Contemporary Society. Theory and Reality
Keywords: seksualność; edukacja seksualna; biografia seksualna; aktywność seksualna; terapia seksualna; promocja zdrowia seksualnego; rozwój seksualny